Development and Evaluation of Improved Feeders for Goats Suitable to Stall-fed Management System (Nepal Agriculture Research Journal, 2010)
Five different types of feeders were designed and tested on goats to find out their effectivenessin reducing feed wastage and cost fabrication. Experiment was conducted at AgricultureResearch Station (ARS)-Bandipur for two years. Tested feeders were hexagonal, rectangular,hay rack, chain barrel and conventional wooden Tatnu. Feeders were fabricated using iron barsand woods. They were tested with the adult goats for feed wastage and feed contamination.Experimental feeds were fodders twigs (Tanki), forage (Stylo, Napier), crop residue (straw fromblack bean) and commercial concentrate. Chain barrel type of feeder was also tested at farmer’sfield at Baradi. Rectangular feeders have significantly lower (P